Overexpression of Orange Carotenoid Protein Protects the Repair of PSII under Strong Light in Synechocystis sp. PCC 6803. (6th November 2018) - Takahashi, Hiroko; Kusama, Yuri; Li, Xinxiang; Takaichi, Shinichi; Nishiyama, Yoshitaka
Abstract: Orange carotenoid protein (OCP) plays a vital role in the thermal dissipation of excitation energy in the photosynthetic machinery of the cyanobacterium Synechocystis sp. PCC 6803. To clarify the role of OCP in the protection of PSII from strong light, we generated an OCP-overexpressing strain of Synechocystis and examined the effects of overexpression on the photoinhibition of PSII. In OCP-overexpressing cells, thermal dissipation of energy was enhanced and the extent of photoinhibition of PSII was reduced. However, photodamage to PSII, as monitored in the presence of lincomycin, was unaffected, suggesting that overexpressed OCP protects the repair of PSII. Furthermore, the synthesis de novo of proteins in thylakoid membranes, such as the D1 protein which is required for the repair of PSII, was enhanced in OCP-overexpressing cells under strong light, while the production of singlet oxygen was suppressed. Thus, the enhanced thermal dissipation of energy via overexpressed OCP might support the repair of PSII by protecting protein synthesis from oxidative damage by singlet oxygen under strong light, with the resultant mitigation of photoinhibition of PSII.